Abnormal Calcium Cycling and Cardiac Arrhythmias Associated With the Human Ser96Ala Genetic Variant of Histidine‐Rich Calcium‐Binding Protein. Issue 5 (14th October 2013) - Singh, Vivek P.; Rubinstein, Jack; Arvanitis, Demetrios A.; Ren, Xiaoping; Gao, Xiaoqian; Haghighi, Kobra; Gilbert, Mark; Iyer, Venkat R.; Kim, Do Han; Cho, Chunghee; Jones, Keith; Lorenz, John N.; et al.
Abstract : Background: A human genetic variant (Ser96Ala) in the sarcoplasmic reticulum (SR) histidine‐rich Ca 2+ ‐binding (HRC) protein has been linked to ventricular arrhythmia and sudden death in dilated cardiomyopathy. However, the precise mechanisms affecting SR function and leading to arrhythmias remain elusive. Methods and Results: We generated transgenic mice with cardiac‐specific expression of human Ala96 HRC or Ser96 HRC in the null background to assess function in absence of endogenous protein. Ala96 HRC decreased (25% to 30%) cardiomyocyte contractility and Ca 2+ kinetics compared with Ser96 HRC in the absence of any structural or histological abnormalities. Furthermore, the frequency of Ca 2+ waves was significantly higher (10‐fold), although SR Ca 2+ load was reduced (by 27%) in Ala96 HRC cells. The underlying mechanisms involved diminished interaction of Ala96 HRC with triadin, affecting ryanodine receptor (RyR) stability. Indeed, the open probability of RyR, assessed by use of ryanodine binding, was significantly increased. Accordingly, stress conditions (5 Hz plus isoproterenol) induced aftercontractions (65% in Ala96 versus 12% in Ser96) and delayed afterdepolarizations (70% in Ala96 versus 20% in Ser96). The increased SR Ca 2+ leak was accompanied by hyperphosphorylation (1.6‐fold) of RyR at Ser2814 by calmodulin‐dependent protein kinase II. Accordingly, inclusion of the calmodulin‐dependent protein kinase II inhibitor KN93 prevented Ser2814 phosphorylation and partially reversed the increases in Ca 2+ spark frequency and wave production. Parallel in vivo studies revealed ventricular ectopy on short‐term isoproterenol challenge and increased (4‐fold) propensity to arrhythmias, including nonsustained ventricular tachycardia, after myocardial infarction in Ala96 HRC mice. Conclusions: These findings suggest that aberrant SR Ca 2+ release and increased susceptibility to delayed afterdepolarizations underlie triggered arrhythmic activity in human Ala96 HRC carriers.